2021
DOI: 10.1108/ijoem-06-2020-0681
|View full text |Cite
|
Sign up to set email alerts
|

The impact of oil price shocks on Turkish sovereign yield curve

Abstract: PurposeThis paper aims to investigate the impact of oil price shocks on the Turkish sovereign yield curve factors.Design/methodology/approachTo extract the latent factors (level, slope and curvature) of the Turkish sovereign yield curve, we estimate conventional Nelson and Siegel (1987) model with nonlinear least squares. Then, we decompose oil price shocks into supply, demand and risk shocks using structural VAR (structural VAR) models. After this separation, we apply Engle (2002) dynamic conditional correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…However, the volatility of commodity prices is likely to affect the household inflation expectations. As discussed earlier, we find that some studies estimate the effect of the volatility of oil prices on other economic variables (Cepni et al , 2020). There exists little evidence regarding the importance of volatility of global commodity prices on household inflation expectations.…”
Section: Literature Reviewsupporting
confidence: 65%
See 1 more Smart Citation
“…However, the volatility of commodity prices is likely to affect the household inflation expectations. As discussed earlier, we find that some studies estimate the effect of the volatility of oil prices on other economic variables (Cepni et al , 2020). There exists little evidence regarding the importance of volatility of global commodity prices on household inflation expectations.…”
Section: Literature Reviewsupporting
confidence: 65%
“…High volatility in the value of a variable creates uncertainty and confusion among firms and consumers about its future path and can affect other related variables (Kumar, 2013). For example, volatility in oil prices affects yield curve (Cepni et al , 2020), exchange rate volatility makes predicting exchange rate difficult (Emenike, 2018) and inflation volatility affects the inflation-output trade-off (Jha and Kulkarni, 2015) and political frustrations or volatility leads to decline in investments [1] (Alon and McKee, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are consistent with those of [ 52 , 53 ], who found that changes in oil market shocks explain BRICs stock returns oil. Market conditional value-at-risk can be used to represent this phenomenon [ 54 ]. study also supports a higher hedging ratio during the global crisis, confirming the oil-stock market's historical performance fluctuations [ 55 ].…”
Section: Results and Analysismentioning
confidence: 99%
“…The hypothesis is supported by the standardized path coefficient of 0.16 between social capital and inventive behavior, which is smaller than 0.05. In conclusion [ 65 ], discovered that information sharing has a favorable impact on creative behavior and that social capital benefits knowledge sharing and innovation. The research supports that social capital and information sharing are crucial in encouraging innovation in public organizations.…”
Section: Resultsmentioning
confidence: 99%